A new nanocomposite assembled with metal organic framework and magnetic biochar derived from pomelo peels: A highly efficient adsorbent for ketamine in wastewater. Issue 5 (October 2021) - Liu, Yan; Cao, Shurui; Xi, Cunxian; Su, Hongtao; Chen, Zhiqiong
Abstract: A new nanocomposite, magnetically modified metal-organic framework ZIF-8/biochar (MZBC), was synthesized and used for removal of emerging contaminant ketamine (KET). Here, ZIF-8 was used as a sacrificial template and magnetic biochar was derived from pomelo peels. The influence of different pyrolysis temperatures (400, 500, 600 and 700 ºС) on adsorption performance was investigated in detail. The optimal pyrolysis temperature for the preparation of MZBC was obtained at 600 ºС. The maximum adsorption capacity of MZBC-600 for KET was 32.50 mg·g −1, which was 24.8 times higher than that of a single magnetic biochar (MBC-600). MZBC-600 exhibited a high stable adsorption capacity for KET over a wide pH (3−12) range and even high ionic strength in water. The pseudo-second-order kinetic model and Freundlich isotherm model were more suitable to analyze the adsorption process of MZBC-600 to KET, with R 2 of 0.996 and 0.998, respectively. Adsorption kinetics, isotherms, pH effect, ionic effect and series of characterization analysis suggested that the adsorption process was dominated by pore filling, π-π interaction, hydrogen bonding and chelation. The sustainable adsorption capacity (>90% of the initial adsorption capacity) of MZBC-600 was well maintained even after five reuse cycles. In a word, this novel nanocomposite (MZBC-600) contributed a high adsorption efficiency, environment-friendliness and good sustainability. Graphical Abstract: ga1 Highlights: A novel bio-nanocomposite of MZBC using ZIF-8 as a sacrificial template was prepared. Pyrolysis temperature of MZBC was a crucial factor for its adsorption of KET. MZBC-600 exhibited a prominent adsorption capacity for KET over a wide pH (3−12) range. Pore filling, π-π, H-bond and chelation interaction are the main adsorption mechanism.